På strejftog indenfor Retskrivningsordbogens territorie. Retskrivningsordbogen 2011 - Jervelund, Anita Ågerup; Schack, Jørgen Schack (Nordiske Studier i Leksikografi, 2007)
The Danish Language Council (Dansk Sprognævn) is preparing a new edition of the official dictionary of Danish orthography (Retskrivningsordbogen). In this paper we discuss some orthographical changes. The changes concern the spelling of words which end in -ium (e.g. akvarium, gymnasium), the spelling of hyphenated compounds like e-mailadresse, S-togs-station, and the spelling of multi-word prepositions like bag ved, inden for. In the new edition of the dictionary, the entry words will contain word-division points. The proposed end-of-line divisions are not the only acceptable ones, and we briefly discuss different principles of word-division (syllabic versus morphemic).